1974
DOI: 10.1080/05698197408981463
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Elevated Ambient Temperatures on the Friction and Wear Behavior of Some Commercial Nickel Base Alloys

Abstract: Measurements of friction and wearduring sliding of specimens of Nimonic 75, C263, Nimonic 108 and Incoloy 901 on like specimens i n air at temperatures from 20 t o 800 C are presented. Under the sliding conditions used, all the alloys show a transition temperature, above which low wear and a low coeficient of friction during sliding are observed after a time and below which these parameters remain relatively high throughout. These temperatures are about 150 C for N75, about 200 C for C263 and N108 and between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1976
1976
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Several studies have shown that cryoprotectant acts as a proleetive agent during heat treatment. Glycerol increases the survival of cultured mammalian cells during hyperthermia [14][15][16][17][18]. Protection of cells from heat by glycerol is thought to result from its ability to stabilize cellular macromolecules [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that cryoprotectant acts as a proleetive agent during heat treatment. Glycerol increases the survival of cultured mammalian cells during hyperthermia [14][15][16][17][18]. Protection of cells from heat by glycerol is thought to result from its ability to stabilize cellular macromolecules [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The development of oxide layers on metal surfaces during sliding often leads to re duced friction and wear (Barnes et al 1977;Bisson i960;Lin et al 1974;S tott et al 1973;S to tt et al 1976;Welsh 1965) and clear th a t such oxides play an im portant p art in various practical wear situations, such as during the operation of gas-turbine engines. There have been relatively few detailed studies of the influence of oxides on friction and wear processes, and rela tively little is known about the modes of formation and operation of such oxides or of their role in reducing friction and wear.…”
Section: Introductionmentioning
confidence: 99%
“…In CE, the use of CDs and their derivatives as chiral selectors is the most common strategy employed for the separation of chiral compounds [1][2][3][4][5]. Enantioseparation of charged compounds has often been achieved with the use of neutral or charged CDs [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], or with dual CD systems consisting of a charged CD and a neutral CD [21][22][23][24][25][26][27][28][29], or two oppositely charged CDs [30]. Among many charged CDs studied to date, sulfated CDs have demonstrated the widest application range [6][7][8].…”
Section: Introductionmentioning
confidence: 99%